CANCER INCIDENCE AMONG POPULATION OF SIBERIA AND RUSSIAN FAR EAST - L. F. Pisareva; I. N. Odintsova; О. A. Ananina; A. P. Boyarkina (Сибирский онкологический журнал)
Evaluation of cancer incidence in a certain area is one of the most important components of cancer control. From 1993 to 2012, a 1.4-fold increase in the annual number of new cancer cases among the population of Siberia and the Far East was registered. The age-standardized incidence rates are increasing with aging of the population. For all cancers, cancer incidence is higher in men than in women with the exception of thyroid and skin melanoma cancer incidence. Six types of cancer incidence curves have been identified: 1) reduction; 2) high growth; 3) relatively uniform growth; 4) reduction followed by stabilization; 5) growth followed by stabilization; 6) relatively uniform increase, then a significant increase.